How flexible and informal arrangements shape the wages of domestic workers in Portugal - Suleman, F.; Figueiredo, M. C. T. (European Society for Population Economics – D5 Labour Market, 2014)
Researchers have long expressed their concern on wage determination but failed in accounting for wages differentials among workers in usually informal and flexible jobs. This paper uses cross-sectional data from a dedicated survey on a sample of domestic workers in Portugal and estimates the impact of contractual arrangements on earnings. Domestic workers contribute to national economies and enable other workers to carry out their own jobs. However, they lack recognition and working conditions, their wages are one of the lowest in the labour market, and are the most vulnerable category of workers. The findings support compensating wage differentials associated with flexible arrangements, but also suggest that domestic workers benefit from declaration of their employment relationship to social security authorities. Additionally, the evidence illustrates penalties for migrant, especially African workers. This paper is connected with international discussion on domestic work and contributes to raise awareness on the role of regulations to promote decent work and reduce inequality.